Lords of Mines and Mills during the First Great Silver Boom of Potosí (1569-1630) - Zagalsky, Paula Cecilia (2023)
This chapter proposes an initial approach to the universe of the so-called "miners" of Potosí, during the first great boom of silver production (1570-1610). The term "miners" refers to a heterogeneous group of owners and lessees of mines and mills, who were part of the world of colonial mining labor. Mexican historiography offers enriching orientations to renew studies on colonial Peruvian mining and its actors. In the case of New Spain, decades of study have given an account of the complex networks of actors involved in mining production, composed of large, medium and small miners. The study of the large New Spanish miners has made it possible to connect them with other social actors and sectors of the colonial economy and to locate their role in the political history of the Hispanic monarchy and its global connections, although these cases, the successful ones, were the exception. The most recent studies have shown that medium and small-scale mining were the majority and fundamental in New Spain. Hence, the study of their characteristics, the conditions in which they worked and particularly their business strategies allow us to appreciate the real conditions of the greater proportion of New Spain´s mining entrepreneurs. For Peru, and Potosí in particular, studies on these subjects are scarce and have tended to concentrate on biographical analyses of individuals belonging to the select and self-styled group of the "azogueros", large multi-implanted miners in various branches of the colonial economy. The most resounding examples have been those of Pedro de Mondragón during the late sixteenth and early seventeenth centuries and Antonio López de Quiroga, during the second half of the seventeenth century. This chapter proposes an approach to this hierarchical and unequal world of miners, which also included women and Indians, during a central period for mining in Potosí, the Americas and globally. The aim is to contribute to the visualization of the great lords of mines and mills, who were part of the complex socio-political and labor dynamics and plots that operated in Potosí, a fundamental center of global silver production during the period.